Análisis y diseño de una infraestructura de redes y gestión para un proyecto con video vigilancia de la ciudadela “Santa Rita” en el cantón Vinces. - Cerezo Gualancañay, Ginger Patricia (2022)
The present work focused on the analysis and design of a network and management infrastructure for a project with video surveillance in the "Santa Rita" citadel of the Vinces canton. The research focused on video surveillance systems as security devices whose objective is control, as well as correct remote and real-time supervision of different areas through the use of multiple strategically placed cameras. Citizen insecurity was taken as the axis of investigation, since this is a problem that affects the entire country, among the factors that influenced the increase in criminal activities is drug use, and the covid-19 pandemic where there was a boom in unemployment cases, and therefore this affects the economic stability of people, which is why people opted for easier solutions to increase their economic income. In the "Santa Rita" citadel of the Vinces canton, there have been acts of insecurity such as robberies, assaults, intrusion into homes, sometimes drug users, among others. Through field research, it was possible to determine the current situation of the citadel and through a bibliographical review in different research sources, the results of implementing video surveillance systems in neighborhood areas were determined, as well as the influence of the design of the infrastructure of network for the proper functioning of security systems.